Transição para coparentalidade e a experiência da parentalidade tardia em casais de dupla carreira - Fidelis, Daiana Quadros (Universidade do Vale do Rio dos Sinos, 2016)
Parenting transition is an important period in the family system and it has been investigated in both national and international contexts for over 30 years. Coparenting is defined as a subsystem involving two or more adults who share parenting a child, nevertheless few national studies on coparenting were carried out. The difficulties in this transition process as well as dual-career demands have led several couples to postpone maternity/paternity, resulting in late gestation. This study aimed to understand coparenting transition in dual-career couples considering late gestation context. The research design encompassed exploratory, descriptive and qualitative methods. Five heterosexual couples married for over two years participated in the study, in which both spouses displayed professional activities and all women got pregnant after aging 35 years old, not undergoing any fertilization procedure. The employed instruments were a sociodemographic questionnaire, a semi-structured interview on co-parenting (NIEPED, 2006) conducted with each couple, and individual interviews were posteriorly scheduled with either mothers or fathers, who answered the Maternity Experience Survey or the Paternity Experience Survey designed by the research group (NUDIF, 1999a; 1999b). The results were split and reported in two empirical papers; the first one was entitled “Late Parenting Experience: Fathers and Mothers’ Perceptions” and the second one was “Conjugality and Late Coparenting in Dual Career Couples”. The data shed light on changes in the transition process, in which both mother and father equally divided the responsibility regarding the child, as well as domestic tasks, reverberating in high conjugal quality levels. Thus, despite changes in couple’s social routine and the substantial weekly workloads faced by them, participants demonstrated adaptability to the transition process.
Keywords: Transição para parentalidade; Coparentalidade; Gestação tardia; Casais com dupla carreira; Parenting transition; Coparenting; Late gestation; Dual-career couples; ACCNPQ::Ciências Humanas::Psicologia